The Effect of Media Education on Adolescent Girls’ Reproductive Hygiene in Rural Area, Indonesia - Andi Angriani Ningsih (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Backgrounds: Genital hygiene should be more maintained because germs are easy to enter and can cause Reproductive Tract Infections. Hygiene during menstruation is a component of personal hygiene that plays an important role in the status of a person's health behavior, including avoiding disturbances in reproductive function. The purpose of this study was to determine the effect of education using the media on the behavior of improving reproductive hygiene for adolescent girls at UPT SMA Negeri 6 Bone Regency. Methods: This type of research is an observational method with a Cross-Sectional Study approach. The population in this study were all adolescent girls X, XI, and XII SMA Negeri 6 Bone Regency as many as 588 people. The sample in this study were all teenage girls X, XI, and XII of SMA Negeri 6 Bone Regency as many as 86 people using a simple random sampling technique. Results: Research shows that there is a significant effect between education using media on the knowledge of young women. There is a significant influence between education using the media on the attitude of young women. There is a significant effect between education using media on the perception of young women. There is a significant influence between education using media on the actions of young women at UPT SMA Negeri 6 Bone Regency. Conclusions: Education affects knowledge, attitude, and perception in adolescents. It is recommended for young women to maintain good personal hygiene in order to avoid various diseases that harms the female reproductive organs.